(Turnitin) THE EFFECT OF RED GUAVA JUICE (PSIDIUMGUAJAVA L.) ON LIPID PROFILE LEVELS IN SERUM - Shahrul Rahman (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2019)
Background: Cardiovascular disease is the highest cause of death in most developing countries.Theincreased cholesterol is the main cause of coronary heart disease and fatty liver disease which increasesthe load / burden of both diseases. One of the alternative that can decrease the cholesterol levels in long term blood plasma isusing the natural ingredients such as guava fruitwhich is known to contained avonoid as antioxidant that can inhibit LDLoxidation so that the levels of LDL can be decreased and atherosclerosis can be prevented as well.Method: The type of research used in this study was experimental research using a pre-test and post-test design without acontrol group, then the study subjects were given 250 ml of red guava fruit juice for 14 days.Results: The results of the study were obtained an average value before treatment (pre test) total cholesterol 204.36 mg / dl, LDL129.08 mg / dl, HDL 58.16 and triglyceride 84.52 and the average value after treatment (post test) total cholesterol 149.88 mg / dl,LDL 82.92 mg / dl, HDL 44.2 mg / dl and triglycerides 104.28.Conclusion: Giving red guava juice can reduce total cholesterol, LDL, HDL, and increase triglyceride levels